Helping Girls with Deafness Victims of Sexual Harassment: REBT with Bisindo as a Mental Health Education Service in Schools - Marlina Marlina; Yuninda Tria Ningsih; Zulian Fikry; Dea Resti Fransiska (Department of Special Education, 2022)
This article examines the girls with deafness in schools who experience sexual harassment. The purpose of this study is to find a post-sexual harassment service model that is in accordance with the characteristics of girls with deafness and explain how schools pay attention to well-organized and theoretical programs using a preventive approach to mental health. Participants totaled 166 users consisting of 105 teachers, 38 students, 8 lecturers, 5 members of organizations for the deaf and other professions. The results showed that sexual harassment can occur physically and verbally towards the girls with deafness which can cause trauma. The girls with deafness are more at risk of being sexually abused than boys. They experienced very significant intimidation. The limited communication characteristics of girls with deafness cause trauma of sexual harassment, irrational beliefs that interfere with social functioning in the environment. There is a need for intervention in special mental health service programs such as REBT with Bisindo that are in accordance with the characteristics of students with deafness. The role of the teacher in preparing children to deal with face life in an increasingly complex society.